(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article provides necessary information about the role of marketing in tourism, the importance of advertising and their interrelationship, and foreign research studies are reviewed, and proposals and recommendations are developed based on them.